Дослідження застосування нейромереж для аналізу ігрового середовища та управління персонажем у тактичній грі - Куртенок, М. Д. (ХНУРЕ, 2025)
This work is dedicated to the development of a tactical tank game utilizing artificial intelligence (AI) for analyzing battle scenarios and making strategic decisions. The aim of this work is to explore how AI can be integrated into gameplay to control enemy behavior dynamically. The research covers the fundamental principles of AI-driven decision-making, including situation analysis, adaptive tactics, and real-time response to battlefield conditions. Furthermore, this work presents a step-by-step approach to implementing AI in tactical game environments. Finally, the study discusses the challenges of AI-driven opponent behavior and potential future improvements in the field.
Keywords: ігрове середовище